STUDENTS’ PERCEPTION TOWARDS ENGLISH E-LEARNING DURING COVID-19 PANDEMIC - Husna Mariyani (STKIP MUHAMMADIYAH SAMPIT, 2022)
This research generally answers a problem as follow: What are students’ perception towards English e-learning during COVID-19 pandemic. This research purpose is to know the students’ perception towards English E-Learning during the COVID-19 pandemic at SMA Negeri 3 Sampit of Eleventh Grade Students at SMA Negeri 3 Sampit in Academic Year 2021/2022. Descriptive analysis research by qualitative descriptive techniques was chosen as an appropriate approach as a type of this research. The researcher used a case study design with a qualitative approach consisting of some data in the form of words, phrases, and sentences. The data was collected through interviews and questionnaires.The result of this research was presented descriptively to reveal the students' perception comprehensively. The research found the students’ have a positive perception about learning English through E-Learning during the COVID-19 pandemic, some of them stated that learning English while at home is quite good and they still get motivated. They argue that this method is arguably quite effective because it is the only way out to keep learning online as long as the COVID-19 pandemic is still taking place in Indonesia, so they can still learn even if not directly in school.